Maerua angolensis Extract Reduces Allodynia and Hyperalgesia in a Mouse Model of Vincristine-Induced Peripheral Neuropathy - Hosea Azi Iliya & , Wonder Kofi Mensah Abotsi, Charles Benneh, Eric Woode (Journal of Applied Pharmaceutical Science, 2016)
Allodynia and hyperalgesia comprise the main and frequent symptoms suffered by patients with neuropathic pain, which responds poorly to therapy. An earlier study reported that stem bark extracts of Maerua angolensis exhibited dose-dependent anti-nociceptive effect against the neurogenic and inflammatory phases of the formalin test. The current study evaluated the effect of petroleum ether/ethyl acetate stem bark extract of Maerua angolensis on vincristine-induced neuropathy. Neuropathic pain was induced by intraperitoneal injection of vincristine (0.1 mg/kg/day) using a 5-day-on, 2-day-off schedule over 12 days. On day 15, baseline responses were measured in the Randall-Selitto mechanical hyperalgesia test and paw withdrawal tests (using Von Frey filaments and cold water at 4.5 °C) and mice that developed allodynia/hyperalgesia were randomly assigned into 7 groups. Normal saline (i.p.), pregabalin (10, 30, and 100 mg/kg, p.o.) and extract (3, 10, and 20 mg/kg, p.o.) were administered to the individual groups. Allodynia/hyperalgesia was measured hourly for 5 hours post treatment. The extract produced significant (P
Keywords: Maerua angolensis, Neuropathic pain, Von Frey filaments, allodynia, hyperalgesia.